Classification of Impacted Third Molars on Conebeam Computed Tomography Images - Niroula, Deepa; Dahal, Sirjana; Poudel, Kalpana; Kumar Singh, Ashutosh; K.C, Krishna (Journal of Nepal Health Research Council, 2025)
Background: An important anatomical factor in injuries to the inferior alveolar nerve is the spatial relationship between the mandibular canal and the corresponding third molars. This study was designed to classify the anatomic three-dimensional relationship between mandibular third molars and the mandibular canal on cone-beam computed tomography mages. Methods: A cross-sectional study was conducted by using CBCT images of 100 individuals visiting the Dental Outpatient Department of X hospital from Jan 2022 – Oct 2022. The images were used to classify the threedimensional relationship between the mandibular canal relative to the roots of the mandibular third molar according to Liqun Gu et al 2018 classification. In this classification, four anatomical positions were considered: buccal, lingual, apical and inter-radicular. The second factor considered was the contact and non-contact relationship between the inferior alveolar nerve canal and the mandibular nerve. The data was analyzed via SPSS version 20. Chi square test was performed to determine the contact relationship of the mandibular third molar root with the mandibular canal. Results: Most of the mandibular canals observed via CBCT (45.0%) were located on the buccal side of the mandibular third molar followed by the apical side (26.0%), between the roots (23.0%) and very few (6.0%) on the lingual side. A significant association was found between the position of the mandibular third molar and the mandibular canal (p<0.001) when the position was lingual and interradicular. Conclusions: The findings of this study revealed that the majority of mandibular third molars were located on the buccal side. There was a significant relationship between the position of the mandibular third molar and the mandibular canal. Keywords: Cone-beam computed tomography; impaction; mandibular canal; third molar.